(untitled) (American Journal of Business Management, Economics and Banking, 2025)
In the context of the global digital economy, the rapid growth of e-commerce is creating demand for new formats and instruments in the financial services market. From this perspective, remote banking services (internet banking, mobile banking, electronic payment systems, and digital wallets) have emerged as an integral part of e-commerce activity. These services facilitate the exchange of goods and services in a digital environment, ensure quick settlements and payments, and help reduce transaction costs in the economy.